Peran Bahasa Indonesia pada Peraturan Daerah Provinsi Gorontalo untuk Mewujudkan Kepastian Hukum - Dali, Meilina Widya; Paki, Sri Yuliani Saputri; Karim, Aprilia Misda Wati; Mahadewi, Chellsea Florenzia; Djafar, Rahmi; Mololonto, Hasra; Sukerta, Zaskia Chika; Kalangit, Obetsius Stive; Pohontu, Ahmad Kamal; Lapananda, Wahyu Ananta; Saidi, Alief Qurrahman H.; Sabah, Mohamad Raditullah H.; Rais, Andika Putra Pratama (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Indonesian plays an important role in the creation of laws and regulations, including regional regulations, as the primary tool for formulating legal norms clearly, firmly, and without producing multiple interpretations. The Regional Regulation of Gorontalo Province as a regional legal product needs to be drafted in good, correct Indonesian, and in accordance with legal language rules in order to realize legal certainty in the implementation of regional government. This study aims to analyze the function of Indonesian in the Regional Regulation of Gorontalo Province, particularly in supporting the clarity of norms and legal certainty. The method used in this study is normative legal research that relies on an approach to legislation and a conceptual approach. The research findings indicate that the application of clear, consistent, and orderly Indonesian in regional regulations has a significant impact on the understanding of legal norms among government officials and the public. Appropriate legal language can avoid ambiguity, variations in interpretation, and the possibility of legal disputes in the implementation of regional regulations. Therefore, optimal use of Indonesian in regional regulations of Gorontalo Province is an important step to ensure legal certainty and increase the effectiveness of regional government implementation.